2019
DOI: 10.1002/wnan.1569
|View full text |Cite
|
Sign up to set email alerts
|

The consolidation of nanomedicine

Abstract: Over the past two decades, nanomedicine has grown steadily, however, without inducing a palpable shift in the diagnosis and treatment of diseases so far. While this may simply be a consequence of the slow, incremental nature that characterizes many modern technologies, this article posits that there is another set of significant factors harboring explanatory power. Uncertainties concerning safety, regulatory, and ethical requirements may have prompted innovators to stay close to the known and approved, eventua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…[ 3 ] Thus, nowadays, with the requirements for more personalized treatments and precision medications, [ 4 ] the interest in these materials to develop multimodal/multifunctional nanosized particles that can perform diagnosis [ 5 ] and different therapies (such as chemo‐, thermo‐, radio‐, immunotherapies) in a single nanoplatform [ 6 ] is continuously growing. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] Thus, nowadays, with the requirements for more personalized treatments and precision medications, [ 4 ] the interest in these materials to develop multimodal/multifunctional nanosized particles that can perform diagnosis [ 5 ] and different therapies (such as chemo‐, thermo‐, radio‐, immunotherapies) in a single nanoplatform [ 6 ] is continuously growing. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…Aside from this, of particular interest to cancer treatment researchers, is the approval of Doxil ® [10] by the Food and Therapeutic Administration (FDA) as the first encapsulated therapeutic, which meant a step forward in the development of new treatments. In fact, it accelerated the registration and marketing approvals of key pharmaceuticals in developed countries [11]. Nanomedicine provides hope to improve current cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 It can reach tumor cells in the vascular endothelial space and undergo a liquid-to-gas phase transition to enhance the ultrasound imaging, so it has been widely used in ultrasound molecular imaging. [16][17][18][19] You et al 20 Prepared a multifunctional Fe3O4-PFH/PLGA nanoparticle, which undergoes a phase change in the PFH core of highly focused ultrasound and can work in synergy with highintensity focused ultrasound to effectively improve the therapeutic effect of tumors. In this study, in vitro targeting experiments showed that many nanoparticles labeled with red fluorescence in the AP-GNP group were tightly attached to the cell membrane surface of MCF-7 labeled with green fluorescence, and some nanoparticles were swallowed.…”
Section: Discussionmentioning
confidence: 99%